2021
DOI: 10.1186/s12864-021-08021-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping uncovers sex-associated copy number variation markers and female hemizygous regions on the W chromosome in Salix viminalis

Abstract: Background Sex chromosomes are in some species largely undifferentiated (homomorphic) with restricted sex determination regions. Homomorphic but different sex chromosomes are found in the closely related genera Populus and Salix indicating flexible sex determination systems, ideal for studies of processes involved in sex chromosome evolution. We have performed genome-wide association studies of sex and analysed sex chromosomes in a population of 265 wild collected Salix viminalis accessions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
(46 reference statements)
0
4
1
Order By: Relevance
“…Of particular interest is the lack of ARR17 or GATA15 homologs on Chr15 in the S. koriyanagi and S. viminalis female genomes. The missing ARR17 in S. viminalis is inconsistent with earlier studies on S. viminalis by Hallingback et al [24] and Almeidia et al [30], which both identified one copy of ARR17 on the S. viminalis Chr15W. The differing number of candidate sex determination genes between species, particularly ARR17 and GATA15, indicates that the mechanism of sex determination may be quite labile within the Vetrix lineage of willows, despite its apparent conservation within the tree willows and the poplars.…”
Section: Sex Determination Genes and Sdr Assemblycontrasting
confidence: 59%
“…Of particular interest is the lack of ARR17 or GATA15 homologs on Chr15 in the S. koriyanagi and S. viminalis female genomes. The missing ARR17 in S. viminalis is inconsistent with earlier studies on S. viminalis by Hallingback et al [24] and Almeidia et al [30], which both identified one copy of ARR17 on the S. viminalis Chr15W. The differing number of candidate sex determination genes between species, particularly ARR17 and GATA15, indicates that the mechanism of sex determination may be quite labile within the Vetrix lineage of willows, despite its apparent conservation within the tree willows and the poplars.…”
Section: Sex Determination Genes and Sdr Assemblycontrasting
confidence: 59%
“…including in the family Salicaceae 13,14 ), and in the genus Fragaria (strawberries), in which a 13-kb transposable "cassette" has moved a currently unidentified female-determining gene(s) to different genomic locations 15 .…”
mentioning
confidence: 99%
“…Prior to the transition, at least five duplicates of small segments of the RR17 gene (‘partial duplicates’) were present on the Y chromosome. The function of these RR17 partial duplicates in Salix is still under investigation 26 , 35 , 37 ; however, inverted repeats of RR17 partial duplicates regulate sex determination via siRNA intermediates in Populus tremula 25 , 26 , which is in the sister genus to Salix , and RR17 partial duplicates in Salix arbutifolia , which also has a 15XY sex determination system, generate siRNAs 25 , 30 , 41 . Interestingly, there is currently no evidence of siRNA expression of RR17 partial duplicates in S. purpurea , so this masculinizing component of the XY system may have been lost or modified in the transition to ZW 39 .…”
Section: Discussionmentioning
confidence: 99%